1994
DOI: 10.1007/bf00563200
|View full text |Cite
|
Sign up to set email alerts
|

Synovial chondromatosis simulating neoplastic degeneration of osteochondroma: findings on MRI and CT

Abstract: A case is presented of synovial chondromatosis within a bursal sac overlying an osteochondroma in a patient with osteochondromatosis. This condition presented with a symptomatic soft tissue mass containing calcified bodies. It can be mistaken clinically and radiographically for malignant degeneration of an osteochondroma with development of chondrosarcoma. Magnetic resonance findings have not previously been described in this entity and proved helpful in the preoperative diagnosis. Magnetic resonance imaging w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

1996
1996
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 6 publications
0
25
0
Order By: Relevance
“…However, the arising of a secondary SC within a bursa overlying an osteochondroma may be still more uncommon; we have found reports of only 7 cases (El-Khouri and Bassett 1978, Borges et al 1981, Schofield et al 1994, Wright et al 1997, Peh et al 1999). In the secondary SC, the loose bodies are within the joint and have the potential for slow growth by synovial metaplasia following proliferation of surrounding connective tissue (Milgram 1977, Villacin et al 1979, Saotome et al 1999.…”
Section: Discussionmentioning
confidence: 85%
See 2 more Smart Citations
“…However, the arising of a secondary SC within a bursa overlying an osteochondroma may be still more uncommon; we have found reports of only 7 cases (El-Khouri and Bassett 1978, Borges et al 1981, Schofield et al 1994, Wright et al 1997, Peh et al 1999). In the secondary SC, the loose bodies are within the joint and have the potential for slow growth by synovial metaplasia following proliferation of surrounding connective tissue (Milgram 1977, Villacin et al 1979, Saotome et al 1999.…”
Section: Discussionmentioning
confidence: 85%
“…CT may be more helpful, showing the lobulated pattern of the calcified nodules lying separately from the exostosis (El-Khouriand Bassett 1978). Post-contrast axial CT scan may show a fluid-filled bursa containing numerous dense loose bodies (Schofield et al 1994). Favoring SC, Peh et al (1999) demonstrated very well how a shift of the cartilaginous nodules can be seen if the patient is examined in prone and supine position.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Subsequently, Milgram and Dunn (19) used the term 'para-articular osteochondroma' to differentiate between intra-articular osteochondroma and synovial osteochondromatosis. Synovial osteochondromatosis typically includes multiple osteochondrous synovium nodules with loose bodies in the joint (21); the multiple lobules of proliferative cartilage originate in the synovial joint tissue. By contrast, para-articular osteochondromas originate from a cartilaginous metaplasia of the articular and para-articular connective tissues (22).…”
Section: A B Cmentioning
confidence: 99%
“…Here, we summarize the progress in the chemical synthesis of GPIs, particularly in the context of development of a general and convergent synthetic strategy. Interested readers are also referred to comprehensive reviews focusing on chemical synthesis of GPI (53)(54)(55). Most syntheses of GPIs were performed in a linear fashion, i.e.…”
Section: Chemical Synthesis Of Protozoan Gpismentioning
confidence: 99%